'Belief' and 'Logos' in the prologue of the Gospel of John : an analysis of complex parallelism - Go, Byung Chan (Stellenbosch : Stellenbosch University, 2009)
Thesis (DTh (Old and New Testament))--Stellenbosch University, 2009.